2018
DOI: 10.1186/s13098-018-0353-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotic supplementation on metabolic status in type 2 diabetic patients with coronary heart disease

Abstract: BackgroundThis study was conducted to evaluate the effects of probiotic supplementation on metabolic profiles in diabetic patients with coronary heart disease (CHD).MethodsThis randomized, double-blind, placebo-controlled trial was performed among 60 diabetic patients with CHD, aged 40–85 years at a cardiology clinic in Kashan, Iran, from October 2017 through January 2018. Patients were randomly divided into two groups to take either probiotic supplements (n = 30) or placebo (n = 30) for 12 weeks. Fasting bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 36 publications
1
48
0
2
Order By: Relevance
“…thermophilus B. lactis L. acidophilus Not known Not known 300 × (3,7 × 10 6 CFU) 300 × (3,7 × 10 6 CFU) 8 BW, BMI, CRP, HbA1c, FPG Moroti et al 40 Brazil 20 T2DM (TC: > 200 mg/dL, TG: > 150 mg/dL, FPG: > 110 mg/dL) L. acidophilus B. bifidum 200 × (1 × 10 8 CFU) 200 × (1 × 10 8 CFU) 4,3 TC, TG, HDL-C, FPG Ostadrahimi et al 41 Iran 60 T2DM (for: < 20 years, FPG: > 125 mg/dL) Strep. thermophiles L. casei L. acidophilus B. lactis Not known 1,200 × (15 × 10 6 CFU) 1,200 × (25 × 10 6 CFU) 1,200 × (8 × 10 6 CFU) 8 BW, TC, TG, LDL-C, HDL-C, HbA1c, FPG Raygan et al 42 Iran 54 T2DM w/ 2- or 3-vessel CHD L. acidophilus L. reuteri L. fermentum B. bifidum 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 12 BW, BMI, TC, TG, LDL-C, HDL-C, CRP, FPG, Insulin, SBP, DBP Raygan et al 43 Iran 60 T2DM w/ 2- or 3-vessel CHD L. acidophilus L. reuteri L. fermentum B. bifidum 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 12 BW, BMI, TC, TG, LDL-C, HDL-C, CRP, FPG, Insulin, SBP, DBP Raygan et al …”
Section: Resultsmentioning
confidence: 99%
“…thermophilus B. lactis L. acidophilus Not known Not known 300 × (3,7 × 10 6 CFU) 300 × (3,7 × 10 6 CFU) 8 BW, BMI, CRP, HbA1c, FPG Moroti et al 40 Brazil 20 T2DM (TC: > 200 mg/dL, TG: > 150 mg/dL, FPG: > 110 mg/dL) L. acidophilus B. bifidum 200 × (1 × 10 8 CFU) 200 × (1 × 10 8 CFU) 4,3 TC, TG, HDL-C, FPG Ostadrahimi et al 41 Iran 60 T2DM (for: < 20 years, FPG: > 125 mg/dL) Strep. thermophiles L. casei L. acidophilus B. lactis Not known 1,200 × (15 × 10 6 CFU) 1,200 × (25 × 10 6 CFU) 1,200 × (8 × 10 6 CFU) 8 BW, TC, TG, LDL-C, HDL-C, HbA1c, FPG Raygan et al 42 Iran 54 T2DM w/ 2- or 3-vessel CHD L. acidophilus L. reuteri L. fermentum B. bifidum 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 12 BW, BMI, TC, TG, LDL-C, HDL-C, CRP, FPG, Insulin, SBP, DBP Raygan et al 43 Iran 60 T2DM w/ 2- or 3-vessel CHD L. acidophilus L. reuteri L. fermentum B. bifidum 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 2 × 10 9 CFU/g 12 BW, BMI, TC, TG, LDL-C, HDL-C, CRP, FPG, Insulin, SBP, DBP Raygan et al …”
Section: Resultsmentioning
confidence: 99%
“…In contradiction with our finding, Lactobacillius, for which we found the association to depend on BMI, was found to be enriched in non-obese controls in comparison to the obese PCOS group in the same study. A randomized controlled study focusing of metabolic benefits synbiotics in PCOS reported that Lactobacillus intake resulted in lower insulin concentration, insulin resistance and higher insulin sensitivity [44] The genera Alkalibacterium and Megasphaera which we found enriched in PCOS samples are also involved in lactic acid fermentation otherwise unknown significance in human gut. Sarcina is a member of the family Clostridiaceae and species from this genus Sarcina ventriculi is an increasingly common grampositive coccus, recognized in gastric biopsies, particularly of patients with delayed gastric emptying [48] .…”
Section: Discussionmentioning
confidence: 65%
“…To date, a few observational studies on the gut microbiome of individuals with PCOS exist [20,22,28,42,43]. Bifidobacterium intake resulted in lower insulin concentration, insulin resistance and higher insulin sensitivity in patients after a 12-week intervention [44]. Relative Bifidobacterium abundance in human gut is known to be driven by lactose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrary to diabetic patients, we did not find any effect of probiotic therapy on carbohydrate metabolism. A study by Raygan et al [ 102 ] which was conducted in patients with type 2 diabetes mellitus (T2DM) and coronary heart disease found that the intervention, during which the strains of Bifidobacterium bifidum , Lactobacillus casei , and Lactobacillus acidophilus were ingested for 12 weeks, significantly decreased the plasma glucose and insulin resistance. In a meta-analysis by Samah et al, [ 103 ] moderately hypoglicaemic properties (lower levels of fasting blood glucose) of microbial agents were confirmed.…”
Section: Discussionmentioning
confidence: 99%